African American Women's Language Use in Response to Male Partners' Condom Negotiation Tactics. Issue 1 (1st January 2018) - Li, Yachao; Samp, Jennifer A.; Coles Cone, Valerie B.; Mercer Kollar, Laura M.; DiClemente, Ralph J.; Monahan, Jennifer L.
Abstract : African American women are vulnerable for sexual health risk; thus, condom use is essential. Guided by research linking goals to communicative content, this study explored women's use of I-, you-, we-, and hedging language during condom negotiation. Female participants ( N = 193) engaged in a condom negotiation role play with male confederates, where language use measures were coded. I-language was used the most frequently. Language use differed as a function of men's tactics, such that women primarily used I-language in response to verbal attacks, you-language in response to seduction, and I- and we-language in response to information seeking. Women who engaged in more recent condom use were more likely to use you-language and, when confederates attacked, they responded with more you-language and less hedging.